2020
DOI: 10.1186/s12884-020-03261-8
|View full text |Cite
|
Sign up to set email alerts
|

“I lost my happiness, I felt half dead and half alive” - a qualitative study of the long-term aftermath of obstetric near-miss in the urban district of Zanzibar, Tanzania

Abstract: Background This study aims to explore the stories of three women from Zanzibar, Tanzania, who survived life-threatening obstetric complications. Their narratives will increase understanding of the individual and community-level burden masked behind the statistics of maternal morbidity and mortality in Tanzania. In line with a recent systematic review of women-centred, qualitative maternal morbidity research, this study will contribute to guidance of local and global maternal health agendas. Methods This two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…We had expected a higher reported rate of impairment based on the anthropological studies done among women who had suffered from severe obstetrical complications in Zanzibar and Burkina Faso. 12 , 13 There are several potential explanations. One is the concept of adaptive preferences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We had expected a higher reported rate of impairment based on the anthropological studies done among women who had suffered from severe obstetrical complications in Zanzibar and Burkina Faso. 12 , 13 There are several potential explanations. One is the concept of adaptive preferences.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Another explanation could be effective social support in Zanzibari society by extended family, community, and religion, including the lived concept of tawakkul , understanding life and its course being in God's hands, motivating a certain mode of perseverance and resilience. 12 In a previous study in Zanzibar, we described a couple, of whom the woman lost her uterus, that adopted the child of a relative. 12 This helped to cope with reproductive loss in a society in which reproduction is valued highly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the authors conclude that with the increasing prevalence of near-miss mothers worldwide 40 as well as in Iran, 41 it is imperative to understand their experience. 42,43 We will probably recognize several limitations inherent in our design. Our study will be conducted at least one year of near-miss experience, sampling of these mothers is hard, given that their number is not too high according to inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The land ownership statistics showed that 58% of fishers have access to of land using for agricultural activities and livestock rearing [30]. However, fishers in Zanzibar have good cooperation in their communities, they help each other, especially during economic crises caused by lean season for fishing [31]. They fully participate in social and communities' issues such as building of schools, mosques and participate in other social activities and development activities [32].…”
Section: Livelihood Of Zanzibar Fishersmentioning
confidence: 99%